2008
DOI: 10.1038/ijo.2008.25
|View full text |Cite
|
Sign up to set email alerts
|

Increased visceral fat and decreased energy expenditure during the menopausal transition

Abstract: Objective: This study assessed longitudinal changes in body composition, fat distribution and energy balance in perimenopausal women. We hypothesized that total fat and abdominal body fat would increase at menopause due to decreased energy expenditure (EE) and declining estrogen, respectively. Design: Observational, longitudinal study with annual measurements for 4 years. Subjects: Healthy women (103 Caucasian; 53 African-American), initially premenopausal. During follow-up, lack of menstruation for 1 year and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
637
12
26

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(742 citation statements)
references
References 35 publications
42
637
12
26
Order By: Relevance
“…The shift toward abdominal obesity after the last menstrual period, which was a general tendency evidenced by former menopausal studies [29,[34][35][36], could not be confirmed in women with early or late menopause in the present analysis. A future longitudinal study of menopausal women's body composition could reveal whether a relation exists between the rates of reproductive ageing, namely the age at menopause and physique as has been evidenced in the case of menarcheal age, the age at the beginning of reproductive capacity [88].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The shift toward abdominal obesity after the last menstrual period, which was a general tendency evidenced by former menopausal studies [29,[34][35][36], could not be confirmed in women with early or late menopause in the present analysis. A future longitudinal study of menopausal women's body composition could reveal whether a relation exists between the rates of reproductive ageing, namely the age at menopause and physique as has been evidenced in the case of menarcheal age, the age at the beginning of reproductive capacity [88].…”
Section: Discussioncontrasting
confidence: 86%
“…However the biological processes that lead to changes in body fat distribution during the menopausal transition, i.e., an increase of total and central body fat (in particular an increase in the accumulation of intra-abdominal fat) and a redistribution of fat from lower body subcutaneous fat toward the abdominal region [29][30][31] have not been fully explored [32,33]. In addition, the changes in body fat distribution by age and during the menopausal transition cannot be studied independently (the increase in relative body fat mass and the increase in abdominal fat accumulation are the main features of body fatness redistribution by ageing) [29,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Women exhibit a tendency toward visceral fat accumulation during the menopausal transition, though it is difficult to separate the influence of menopause from the natural tendency toward fat accumulation with age 6, 28. Certainly, mice that are deficient in estradiol (because of a genetic deletion of the gene for aromatase) exhibit an increase in visceral fat and resultant insulin resistance compared with their wild‐type counterparts 29.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that there are many benefits of exercise on bone [33], cardiovascular, metabolic [34,35], diabetes [36], cancer, longevity [37], psychological well being [38,39] and overall quality of life [26]. Hence, it is appropriate for women to be physically active throughout the menopausal transition and afterwards.…”
Section: The Benefits Of Exercise For Overall Wellbeingmentioning
confidence: 99%